Synthesis and characterisation of group nine transition metal complexes containing new mesityl and naphthyl based azaindole scorpionate ligands - Owen, Gareth R.; Tsoureas, Nikolaos; Hope, Rebecca F.; Kuo, Yu Ying; Haddow, Mairi F. (Dalton Transactions, 2011)
Two novel boron-based flexible scorpionate ligands based on 7-azaindole, Li[HB(azaindolyl)2(1-naphthyl)] and Li[HB(azaindolyl) 2(mesityl)] {Li[NaphthBai] and Li[MesBai] respectively}, have been prepared (mesityl = 2,4,6-trimethylphenyl). These salts have been isolated in two forms, either as dimeric structures which contain bridging hydride interactions with the lithium centres or as crystalline material containing mono nuclear bis-acetonitrile solvates. The newly formed ligands have been utilised to prepare a range of group nine transition metal complexes with the general formula [M(COD){κ3-NNH-HB (azaindolyl)2(Ar)}] (where M = rhodium, iridium; Ar = 1-naphthyl, mesityl; COD = 1,5-cyclooctadiene) and [Rh(NBD){κ3-NNH-HB (azaindolyl)2(Ar)}] (where NBD = 2,5-norbornadiene; Ar = 1-naphthyl, mesityl). These new complexes have been compared to the previously reported compounds which contain the related scorpionate ligands Li[HB(azaindolyl) 2(phenyl)] and K[HB(azaindolyl)3] {Li[PhBai] and K[Tai] respectively}. Structural characterisation of the complexes [Rh(COD){κ3-NNH-HB (azaindolyl)2(mesityl)}], [Ir(COD){κ3-NNH-HB (azaindolyl)2(mesityl)}] and [Rh(NBD){κ3-NNH-HB (azaindolyl)2(naphthyl)}] confirm the expected κ3-NNH coordination mode for these new ligands. Spectroscopic analysis suggests strong interactions of the B-H functional group with the metal centres in all cases. © 2011 The Royal Society of Chemistry.